Maternal Filarial Infection Influences the Development of Regulatory T Cells in Children from Infancy to Early Childhood. - Madhusmita Bal; Manoranjan Ranjit; K Gopinath Achary; Ashok K Satapathy (Public Library of Science (PLoS), 2016)
BACKGROUND:Children born from filarial infected mothers are comparatively more susceptible to filarial infection than the children born to uninfected mothers. But the mechanism of such increased susceptibility to infection in early childhood is not exactly known. Several studies have shown the association of active filarial infection with T cell hypo-responsiveness which is mediated by regulatory T cells (Tregs). Since the Tregs develop in the thymus from CD4+ CD25hi thymocytes at an early stage of the human fetus, it can be hypothesized that the maternal infection during pregnancy affects the development of Tregs in children at birth as well as early childhood. Hence the present study was designed to test the hypothesis by selecting a cohort of pregnant mothers and children born to them subsequently in a filarial endemic area of Odisha, India. METHODOLOGY AND PRINCIPAL FINDING:A total number of 49 pregnant mothers and children born to them subsequently have been followed up (mean duration 4.4 years) in an area where the microfilariae (Mf) rate has come down to <1% after institution of 10 rounds of annual mass drug administration (MDA). The infection status of mother, cord and children were assessed through detection of microfilariae (Mf) and circulating filarial antigen (CFA). Expression of Tregs cells were measured by flow cytometry. The levels of IL-10 were evaluated by using commercially available ELISA kit. A significantly high level of IL-10 and Tregs have been observed in children born to infected mother compared to children of uninfected mother at the time of birth as well as during early childhood. Moreover a positive correlation between Tregs and IL-10 has been observed among the children born to infected mother. SIGNIFICANCE:From these observations we predict that early priming of the fetal immune system by filarial antigens modulate the development of Tregs, which ultimately scale up the production of IL-10 in neonates and creates a milieu for high rate of acquisition of infection in children born to infected mothers. The mechanism of susceptibility and implication of the results in global elimination programme of filariasis has been discussed.